Vibration of core subassemblies due to large sodium–water reaction in the steam generator of a Liquid Metal Fast Breeder Reactor. (July 2018) - Sumathi, V.; Jalaldeen, S.; Selvaraj, P.; Murugan, S.
Abstract: In a Liquid Metal cooled Fast Breeder Reactor (LMFBR), liquid sodium is used as the reactor coolant to extract the heat energy from the core of the reactor. Liquid sodium has a chemical characteristic that makes it to violently react with water or steam. When large sodium-water reaction occurs due to defect, leakage or breakage in the steam generator tubes, high pressure waves will be generated and get transmitted throughout the secondary sodium circuit and interact with the components like sodium headers on top/bottom of steam generator, surge tank, intermediate heat exchanger etc., which also affects the safety of primary sodium circuit and core subassemblies. In LMFBR, sodium water reactions are included in the Design Basis Events. This dynamic event needs to be analyzed from the perspective of integrity of core subassemblies considering the phenomenon of fluid structure interaction. To evaluate the integrity of core subassemblies, the behavior of high pressure waves at intermediate heat exchanger is considered and the response of the subassemblies to the dynamic pressure load has been studied. The dynamic analysis of the reactor model is carried out using a three-dimensional finite element analysis in CAST3M computer code. In the code, the fluid elements are represented by volume elements and the coupling between fluid and structure by surface elements. Fluid damping is considered in the simulation. Validation of the code has been carried out using an experimental setup. Analysis results shows the maximum displacement of the primary circuit components viz., IHX, Inner vessel and subassemblies are 5.0 mm, 2.0 mm and 0.07 mm respectively for a design basis sodium water reaction event. Due to this displacement there is negligible change in the reactivity of the core. Graphical abstract: Image 1 Highlights: In pool type fast reactors, Intermediate Heat Exchangers are supported at the top and middle. During large sodium water reaction, due to transmission of pressure waves the Intermediate Heat Exchangers can vibrate. The integrity of core subassemblies due to Intermediate Heat Exchangers vibration is studied. The dynamic analysis of the reactor model is carried out using a 3-D FEM analysis in CAST3M computer code.